1998
DOI: 10.1002/pro.5560070424
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X‐ray analysis of a 1:1 complex between a designed monomeric interferon‐gamma and its soluble receptor

Abstract: Abstract:A variant of human interferon-gamma (IFN-y) has been created in which the two chains of the homodimeric cytokine were linked N-to C-terminus by an eight residue polypeptide linker. The sequence of this linker was derived from a loop in bira bifunctional protein, and was determined from a structural database search. This "single-chain" variant was used to create an IFN-y molecule that binds only a single copy of the a-chain receptor, rather than the 2 a-chain receptor: 1 IFN-y binding stoichiometry obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…[39] In this respect, proven polymersomes concepts, such as targeting, may also lead to a fast development of advanced peptosomes. [40,41] Peptide Beads Peptide beads are spherical particles in the submicrometer range, formed by self-assembly of the amphiphilic peptide Ac-X 3 -gT and its close analogues AcC-X 3 -gT, AcC(sl)-X 3 -gT, and Ac-X 3 -gT-C. [13,14] To obtain information about the underlying structure and formation process, we extensively characterized the beads by microscopic and light scattering (LS) techniques, such as AFM, TEM, SEM, SLS and DLS. In summary, the beads exhibited a particle scattering factor and a ρ-parameter (R g /R h ) that confirm the beads to be solid spheres.…”
Section: Micelles and Fibersmentioning
confidence: 99%
“…[39] In this respect, proven polymersomes concepts, such as targeting, may also lead to a fast development of advanced peptosomes. [40,41] Peptide Beads Peptide beads are spherical particles in the submicrometer range, formed by self-assembly of the amphiphilic peptide Ac-X 3 -gT and its close analogues AcC-X 3 -gT, AcC(sl)-X 3 -gT, and Ac-X 3 -gT-C. [13,14] To obtain information about the underlying structure and formation process, we extensively characterized the beads by microscopic and light scattering (LS) techniques, such as AFM, TEM, SEM, SLS and DLS. In summary, the beads exhibited a particle scattering factor and a ρ-parameter (R g /R h ) that confirm the beads to be solid spheres.…”
Section: Micelles and Fibersmentioning
confidence: 99%
“…Our computational predictions are based on the analysis of crystal structures of complexes between IFN γ and the extracellular part of IFN γ R1, namely, the structures of PDB codes 1fg9 [ 19 ] and 1fyh [ 20 ] that contain four crystallographically independent IFN γ /IFN γ R1 complexes. Throughout the paper, IFN γ R1 residues are numbered as in UniProt entry P15260.…”
Section: Methodsmentioning
confidence: 99%
“…IFN γ R1 models are based on PDB structures 1fg9 [ 19 ] and 1fyh [ 20 ]. Missing residues in both structures were added using Modeller suite of programs [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that IFN-possesses high binding affinity (K d = 10 À8 -10 À10 M) for IFNGR1 (Marsters et al, 1995;Green et al, 1998). The IFN-dimer can also directly interact with IFNGR1 (Ealick et al, 1991;Fountoulakis et al, 1992;Chè ne et al, 1995), as shown by the solution of the crystal structure of their complex Randal & Kossiakoff, 1998;Acebró n et al, 2009). Furthermore, specific interaction of IFN-with its receptors is crucial in the IFN-/signal transducer and activator of transcription (STAT) signalling pathway cascade.…”
Section: Introductionmentioning
confidence: 99%